Cultivo en efluentes urbanos del alga Scenedesmus quadricauda (Sphaeropleales: Scenedesmaceae) y su potencial para biodiesel: perfil de ésteres metílicos de ácidos grasos (UNED Research Journal, 2014)
Microalgae stand as biodiesel feedstock for high productivity and good quality of lipids. This paper presents the fatty acid methyl ester profile of Scenedesmus quadricauda. The culture was grown in Trelew city sewage, Patagonia, Argentina, in 20L at 23±1ºC, 12:12 photoperiod, fluorescent lighting tubes at 33μE m-2s-1 and agitation by air bubbling. Percentage of fatty acid methyl esters was 7,89%, it was determined by Lepage method. The profile was obtained by gas chromatography. Methyl linolenate (C18: 3) and polyunsaturated (≥4 double bonds) ester fractions were 15,06% and 0,83% respectively. The unsaturation index (0,84) was estimated and some biodiesel parameters were calculated through it: kinematic viscosity (4,68mm s -2), iodine value (75,15), cetane number (57,28), cloud point (8,78°C), specific gravity (0,88) and higher heating value (40,01MJ/kg). Linolenic acid ester fraction is above the limit value of EN 14214:2003 (
Keywords: biodiesel; microalgae; Scenedesmus quadricauda; urban effluents; fatty acid methyl esters.